Highly Efficient Synthesis of Allopurinol Locked Nucleic Acid Monomer by C6 Deamination of 8-Aza-7-bromo-7-deazaadenine Locked Nucleic Acid Monomer - Kosbar, Tamer; Sofan, Mamdouh; Abou-Zeid, Laila; Waly, Mohamed; Pedersen, Erik B. (Synthesis, 2013)
An allopurinol locked nucleic acid (LNA) monomer was prepared by a novel strategy through C6 deamination of the corresponding 8-aza-7-bromo-7-deazaadenine LNA monomer with aqueous sodium hydroxide. An 8-aza-7-deazaadenine LNA monomer was also synthesized by a modification of the new synthetic pathway. N-Glycosylation at the 8-position was prevented by steric hindrance from the 7-bromo atom in the starting material 8-aza-7-bromo-7-deazaadenine. In the final step of the synthesis, the bromine was removed together with a benzyl protecting group by catalytic reduction with ammonium formate to give the required LNA monomers.
Keywords: glycosylations; nucleobases; nucleosides; regioselectivity